Advantages Of The Neutron-Activation Method In Diagnosing Microelement Deficiency In Patients Recovered From Covid-19 (Texas Journal of Medical Science, 2025)
This article discusses the advantages of neutron-activation analysis (NAT) in diagnosing microelement deficiencies in children who have recovered from COVID-19. NAT possesses high sensitivity and allows for the simultaneous detection of 22 elements in hair samples. According to dissertation results, in 112 children, zinc (Zn) decreased by 1.6 times (54.61±1.7 mcg/g), iron (Fe) by 2.2 times (9.09±0.29 mcg/g), and polymicroelementosis was detected in 89.3% of cases. The non-invasiveness and accuracy of NAT make it an important tool in pediatric diagnostics. An algorithm developed based on NAT during the recovery period (DGU №34416) has demonstrated confirmed effectiveness